2018
DOI: 10.4103/jnrp.jnrp_269_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiologic Profile of Pediatric Traumatic Brain Injury in Western Rajasthan

Abstract: Objective:The aim of this study was to evaluate clinico-radiological profile and outcome of pediatric traumatic brain injury (TBI).Design:Prospective observational studySetting:Intensive Care Unit, ward and OPD of Pediatrics, Dr. S. N. Medical College, Jodhpur (tertiary care hospital).Participants:A total of 188 children (1 month–18 years) were enrolled and 108 admitted.Intervention:TBI classified as mild, moderate, or severe TBI. Neuroimaging was done and managed as per protocol. Demographic profile, mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Focusing on mortality the data shows that 24 patients expired, out of which 21 had severe head injury. It again signals that GCS as a predictor of outcome, similarly shown by study from Dara et al 2…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Focusing on mortality the data shows that 24 patients expired, out of which 21 had severe head injury. It again signals that GCS as a predictor of outcome, similarly shown by study from Dara et al 2…”
Section: Discussionsupporting
confidence: 70%
“…This difference may be there because of difference in age distribution. 2,3 It is noticed that 33% of this population accounts for severe head injury, while Garg et al reported 47% as severe one, while Dara et al reported it to be about 22%. The CT scan finding clearly points that skull fractures (88 patients) are far more common than contusion (53 patients).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations